2012
DOI: 10.1111/j.1468-1293.2012.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of urinary albumin and total protein may facilitate decision‐making in HIV‐infected patients with proteinuria

Abstract: ObjectiveWe recently showed that a urine albumin/total protein ratio (uAPR) < 0.4 identifies tubular pathology in proteinuric patients. In tubular disorders, proteinuria is usually of low molecular weight and contains relatively little albumin. We tested the hypothesis that uAPR is useful in identifying tubular pathology related to antiretroviral use in HIV-infected patients. MethodsWe retrospectively identified urine protein/creatinine ratios (uPCRs) in HIV-infected patients. A subset of samples had uPCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…We observed that the prevalence of glomerular and tubular proteinuria in our sample was close, 7.9 and 10.8%, respectively. This frequency of glomerular proteinuria is in accordance with other published data [4,5,12,31,32]. Studies that have attempted to evaluate glomerular and tubular proteinuria simultaneously during HIV infection are however scarce in the literature.…”
Section: Discussionsupporting
confidence: 78%
“…We observed that the prevalence of glomerular and tubular proteinuria in our sample was close, 7.9 and 10.8%, respectively. This frequency of glomerular proteinuria is in accordance with other published data [4,5,12,31,32]. Studies that have attempted to evaluate glomerular and tubular proteinuria simultaneously during HIV infection are however scarce in the literature.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, early stages of CKD are defined by kidney damage, assessed through abnormal presence of urinary markers (protein, albumin), without alteration of the GFR. The early screening of glomerular or tubular proteinuria in HIV-infected patients using a simple method [16] can help identify factors associated with subclinical renal injury, hence to implement preventive or corrective measures. However, studies evaluating the prevalence and the determinants of proteinuria in HIV-infected patients are limited.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] indicates glomerular proteinuria, while a ratio lower than 0.4 is a marker of tubular proteinuria. 27 Tubular proteinuria can also be detected by specific markers such as urinary excretion of retinol binding protein, α-1-microglobulin, β-2-microblobulin, and NGAL (neutrophil gelatinaseassociated lipocalin). 28 These are sensitive markers of tubular damage, yet are not readily available in all clinical labs.…”
Section: Problem Of Renal Function Monitoringmentioning
confidence: 99%